IS DOSE TITRATION REQUIRED FOR ANTIHYPERTENSIVE AGENTS IN GERIATRIC DIABETIC PATIENTS? - Shastry, Rajeshwari; M R Adhikari, Prabha; D Ullal, Sheetal; N. Chowta, Mukta; D Acharya, Sahana (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to evaluate the antihypertensive drug usage and dosage differences between geriatric and non-geriatric diabetics with reference to the duration of hypertension and creatinine clearance (Crcl). Methods: In this observational study, patients with type 2 diabetes mellitus were grouped into geriatric (age ≥60 years) and non-geriatric (age <60 years). Patients' demographic data, duration of hypertension, drugs prescribed, and serum creatinine were recorded after the patients had a stabilized antihypertensive dose for 6 months. Crcl was calculated using Cockcroft–Gault formula. The dosages of antihypertensives were converted into equivalent doses for easy comparison within a group. For angiotensin-converting enzyme inhibitors (ACEIs), enalapril was considered as prototype, and for angiotensin receptor blockers (ARBs) losartan, beta-blocker atenolol, and calcium channel blockers (CCBs), amlodipine was considered as prototype. Univariate analysis was done for comparison of drug doses between groups. Results: A total of 336 diabetics with hypertension were included, of which 252 were geriatric and 84 non-geriatric. Duration of hypertension was expectedly longer in the geriatric group (8.40±7.26 vs. 5.46±5.67; p=0.001). Systolic blood pressure was higher in geriatrics (137.14±13.51 vs. 133.38±12.49; p=0.01). When adjusted for the duration of hypertension and Crcl, there were no significant differences in the mean converted equivalent doses of beta-blockers, CCBs, ARBs, and hydrochlorothiazide between geriatrics and non-geriatrics. However, statistically significant lower converted equivalent doses of all ACEIs were needed in geriatrics compared to non-geriatrics, when adjusted for duration of hypertension and Crcl. Enalapril required 20.57% and ramipril required 18.36% dose reduction in geriatrics compared to non-geriatrics. Conclusion: A 20% dosage reduction is needed for ACEIs in the elderly.